(untitled) (American Journal of Islam and Society, 1989)
Introduction Jean Baudrillard suggested we "forget Foucault" because his status as one of the greatest thinkers of the West in this century belied his commitment against state power. A similar criticism may be levied against Habermas, whose ideal communication community merely reproduces and perpetuates so-called modern secular Western epistemologies. If we take seriously the anarchic thought of Habermas and Foucault, we conclude that the epistemologies created in the past few hundred years are pernicious, pervasive, and truth-distorting. But their vision of the possible world which would emerge after the death of these epistemologies is extremely restricted and inadequate. I suggest we "remember" Islam as the divine guidance of God (SWT), which provides the basis for a truly emancipatory meta-critique. The extension of an Islamic critique into the realm of anarchic thought gives it more precision and sophistication. Social and Natural Sciences: The Islamic Perspective [1981] lays the foundation for an Islamic critique of Western episternologies and the rebuilding of the Islamic sciences by exposing the inadequacies of Western epistemologies and by outlining the guidelines along which Islamic epistemologies must direct the intellectual power of Muslim scholars. The contributors to Social and Natural Sciences denounce the modernized and socialized versions of Islam arising in this century. These versions borrowed their essence not from Islam but from the capitalist, neo-colonial West or from the Marxist-Leninist East. I suggest we characterize the first part of this Islamic critical endeavor as anarchic in that it recognizes the Western epistemologies are neither benign nor local, but in fact carry interest-full, imperialist, dominating designs on ...